Synthesis, Photophysics, and Electronic Structures of Benzene‐Linked Bispyrimidine Compounds. Issue 4 (12th February 2015) - Song, Guangliang; Liu, Rui; He, Guangke; Yuan, Shidong; Zhu, Hongjun
Abstract Seven multi‐dipole and multibranched benzene‐linked bispyrimidine derivatives containing a two‐layer binary tree structure with different electron donor and acceptor groups were designed, synthesized, and characterized. The influences of substituents and solvents on the optical properties of the compounds were investigated. The UV/vis absorption (λabsmax: 311–371 nm), PL emission (λemmax: 386–527 nm), stokes shift (2864–6414 cm−1), and fluorescence quantum yield (Φf: 0.01∼0.16) of the compounds in CH3CN solution are influenced by the electron‐donor or accept substituents. The absorption and emission spectra of the compound with the highest Φf in various solvents indicate that the solvent has little influence on absorption spectrum but does influence the emission spectrum. Transient absorption spectra exhibiting strong positive absorption bands in the near‐IR wavelength means that these compounds could potentially be used as optical limiting materials, which is further confirmed by the quantum chemical calculations.